Heat-Shock Induces Granule Cell Dispersion and Microgliosis in Hippocampal Slice Cultures - Weninger, Jasmin; Meseke, Maurice; Rana, Shaleen; Förster, Eckart (Frontiers in Cell and Developmental Biology, 2021)
Granule cell dispersion (GCD) has been found in the dentate gyrus (dg) of patients with temporal lobe epilepsy and a history of febrile seizures but was recently also observed in pediatric patients that did not suffer from epilepsy. This indicates that GCD might not always be disease related, but instead could reflect normal morphological variation. Thus, distribution of newborn granule cells within the hilar region is part of normal dg development at early stages but could be misinterpreted as pathological granule cell dispersion. In turn, pathological granule cell dispersion may be caused, for example, by genetic mutations, such as the reeler mutation. Granule cell dispersion in the reeler mutant goes along with an increased susceptibility to epileptiform activity. Finally, pathological granule cell dispersion in combination with epilepsy is caused by experimental administration of the glutamate receptor agonist kainic acid in rodents. In consequence, the interpretation of GCD and the role of febrile seizures remains controversial. Here, we asked whether febrile temperatures alone might be sufficient to trigger GCD and used hippocampal slice cultures as in vitro-model to analyze the effect of a transient temperature increase on the dg morphology. We found that a heat-shock of 41 °C for 6 hours was sufficient to induce GCD and degeneration of a fraction of granule cells. Both of these factors, broadening of the granule cell layer and increased neuronal cell death within the granule cell layer, contributed to development of a significantly reduced packaging density of granule cells. In contrast, Reelin expressing Cajal-Retzius (CR) cells in the molecular layer were heat-shock resistant. Thus, their number was not reduced, and we did not detect degenerating CR cells after heat-shock, implying that GCD was not caused by the loss of CR cells. Importantly, the heat-shock induced deterioration of dg morphology was accompanied by a massive microgliosis, reflecting a robust heat-shock induced immune response. In contrast, in the study that reported on granule cell dispersion as a non-specific finding in pediatric patients, no microglia reaction was observed. Thus, our findings underpin the importance of microglia as a marker to distinguish pathological GCD from normal morphological variation.